Hypoglossal Nerve Schwannoma in the Submandibular Region: A Case Report and Discussion - Saima Tabassum; Manish Gupta (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Schwannomas of head and neck regioncommonly arise from the vestibular and vagus nerve. Hypoglossal nerve schwannomas are very rare. They may be intracranial only or have both intra and extracranial extension. Radiology specially, computed tomography (CT) and magnetic resonance (MRI) are useful in not only diagnosis but also identifying the nerve of origin. Total excision of the tumor via an external approach is the treatment of choice, for extracranial hypoglossal nerve schwannoma.